Experiential Marketing - Exploring New Horizons - Nikalje, Vaishalli; Guruprasad, M. (Indian Journal of Marketing, 2010)
Experiential marketing is more than an opportunity to show off all the bells and whistles of a product. "It’s all about emotions and feelings, achieving some sort of feeling." A person today is bombarded with different kinds of advertising at every turn. May it be the grocery store, the side of the buildings, email boxes and every place in between. People in today’s society are too busy with their weekly calendars loaded with more things that they can do in a month. An average person receives about a few hundreds of marketing messages per day. These messages are greatly reducing the effectiveness of traditional advertising. Managers feel it is no longer enough to have functional features, benefits and quality - but you also need to provide great experience to your customers. What is needed is a way to reach potential customers that grab them emotionally and personally-connecting them to a brand for life. Experience is on the hottest topics today in Marketing Management.